Postgraduate year two pharmacy residents' perceptions of pursuing board certification during residency training. Issue 2 (23rd October 2019) - Roberts, Megan Z.; Manis, Melanie M.; Sebaaly, Jamielynn C.; Tran, Emmeline
Abstract: Introduction: The Board of Pharmacy Specialties (BPS) offers pharmacists an opportunity to obtain post‐licensure certification in various specialty pharmacy practice areas. Each BPS specialty has specific eligibility requirements. The Pharmacotherapy specialty is unique in that it does not require candidates who have completed a postgraduate year one (PGY1) residency program to demonstrate additional practice experience or training to pursue this board certification. Thus, all postgraduate year two (PGY2) pharmacy residents would be eligible to sit for the Board Certified Pharmacotherapy Specialist (BCPS) examination during their PGY2 training. Objectives: The objective of this study was to identify PGY2 pharmacy residents' perceptions of pursuing board certification during residency training. Methods: An electronic survey was developed, pilot tested, and sent to PGY2 pharmacy residents completing PGY2 training from 2015 to 2019 at 12 pharmacy residency programs across the United States. Results: A total of 116 responses were obtained (estimated response rate 16%, n = 116 of 706). Among respondents, 38% pursued BCPS certification during PGY2 training and all achieved a passing examination score. The majority of these individuals (93%) were satisfied with their decision to obtain BCPS designation. Of the 72 respondents who did not pursue BCPS designation during PGY2 training, 96% were satisfied with their decision to not take the examination as a PGY2 resident. Conclusion: Among a cohort of current and former PGY2 pharmacy residents, over a third were successful in pursuing and obtaining BCPS designation during their PGY2 residency year. This indicates that board certification may be feasible during PGY2 training. Nearly all respondents were satisfied with their decision to pursue or not pursue BCPS designation as a PGY2 resident.